2020
DOI: 10.1371/journal.pone.0235165
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting preferences for outpatient care experiences in Hungary: A discrete choice experiment with a national representative sample

Abstract: Introduction Patient-reported experience measures (PREMs) are central to inform on the responsiveness of health systems to citizens' health care needs and expectations. At their current form, PREMs do not reflect the weights that patients assign to varying aspects of the care experience. We aimed to investigate patients' preferences and willingness to pay (WTP) for attributes of the care experience in outpatient settings. Methods A discrete choice experiment was conducted among a representative sample of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Third, contextual factors, such as country-specific legislation, data protection regulation, the organization of the healthcare system, and market competition may influence the diffusion of the use of patient-reported data across a health insurer's business. As suggested by Klose et al (2016) [80] and Brito Fernandes et al (2020) [8], the knowledge about patients' needs, preferences, and experiences could help organizations such as health insurers in developing and optimizing a patient-centered approach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, contextual factors, such as country-specific legislation, data protection regulation, the organization of the healthcare system, and market competition may influence the diffusion of the use of patient-reported data across a health insurer's business. As suggested by Klose et al (2016) [80] and Brito Fernandes et al (2020) [8], the knowledge about patients' needs, preferences, and experiences could help organizations such as health insurers in developing and optimizing a patient-centered approach.…”
Section: Discussionmentioning
confidence: 99%
“…fit for risk-adjustment or a people-centered approach to developing such measures) offer another layer of complexity to the conceptualizations of such data. This context also sets the opportunity for new measures to arise, such as that of patient-reported outcome-based performance measures [51,56] and preference-based PREMs [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, considering the cultural context, the weight citizens assign to waiting time attributes is relatively small compared to that of other features of health care services (e.g., a doctor providing easy to understand explanations, or involving the patient in decision-making about care/treatment). Recent evidence from a discrete choice experiment in which the full sample of the survey ‘Patient experiences in health care’ was used, showed that respondents’ willingness to pay varied from €4.38 to wait an hour less at a doctor’s office to €5.46 for one week reduction in the waiting time for an appointment; by comparison, other attributes of the care experience were highly valued (e.g., on average, respondents were willing to pay €36.13 more to have an appointment with a doctor that spends enough time in consultation with a patient) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%